Prospective associations of maternal choline status with offspring body composition in the first 5 years of life in two large mother–offspring cohorts: the Southampton Women’s Survey cohort and the Growing Up in Singapore Towards healthy Outcomes cohort - van Lee, Linde; Crozier, Sarah R; Aris, Izzuddin M; Tint, Mya T; Sadananthan, Suresh Anand; Michael, Navin; Quah, Phaik Ling; Robinson, Sian M; Inskip, Hazel M; Harvey, Nicholas C; Barker, Mary; Cooper, Cyrus; et al. (International journal of epidemiology, 2019)
Abstract Background Choline status has been positively associated with weight and fat mass in animal and human studies. As evidence examining maternal circulating choline concentrations and offspring body composition in human infants/children is lacking, we investigated this in two cohorts. Methods Maternal choline concentrations were measured in the UK Southampton Women’s Survey (SWS; serum, n = 985, 11 weeks’ gestation) and Singapore Growing Up Towards healthy Outcomes (GUSTO); n = 955, 26–28 weeks’ gestation) mother–offspring cohorts. Offspring anthropometry was measured at birth and up to age 5 years. Body fat mass was determined using dual-energy x-ray absorptiometry at birth and age 4 years for SWS; and using air-displacement plethysmography at birth and age 5 years for GUSTO. Linear-regression analyses were performed, adjusting for confounders. Results In SWS, higher maternal choline concentrations were associated with higher neonatal total body fat mass {β = 0.60 standard deviation [SD]/5 µmol/L maternal choline [95% confidence interval (CI) 0.04–1.16]} and higher subscapular skinfold thickness [β = 0.55 mm/5 µmol/L (95% CI, 0.12–1.00)] at birth. In GUSTO, higher maternal choline concentrations were associated with higher neonatal body mass index-for-age z-score [β = 0.31 SD/5 µmol/L (0.10–0.51)] and higher triceps [β = 0.38 mm/5 µmol/L (95% CI, 0.11–0.65)] and subscapular skinfold thicknesses [β = 0.26 mm/5 µmol/L (95% CI, 0.01–0.50)] at birth. No consistent trends were observed between maternal choline and offspring gain in body mass index, skinfold thicknesses, abdominal circumference, weight, length/height and adiposity measures in later infancy and early childhood. Conclusion Our study provides evidence that maternal circulating choline concentrations during pregnancy are positively associated with offspring BMI, skinfold thicknesses and adiposity at birth, but not with growth and adiposity through infancy and early childhood to the age of 5 years.